The Role of English Teachers in Guiding Students to Win the English Debat Competition - Wiradarsia Wiradarsia; Potjut Ernawati; Asnawi Muslem (Universitas Syiah Kuala, 2017)
This study aims at investigating empirical data on the role of the English teachers in guiding the students to win the English competition in the form of qualitative study. The study was carried out at SMPN 19 Percontohan Banda Aceh in February 2016. The objective of this study was to identify the roles the English teachers. The roles of the teacher were adapted from Harden and Crosby those roles include information provider, model, facilitator, assessor, planner, and resource material creator. The sources of the data were from informants and classroom observation and the data were collected through observation and interview. In analysing the data, the writer used interactive model analysis including reducing the data, presenting the data, and drawing conclusion. The results of this study indicate that the roles of the English teacher of Percontohan Junior High School play a big contribution on students’ success in winning the English contest competition. Besides, this school provided extracurricular clubs which help students to improve and increase their skill.